The structure and musical styles of bilingual musical theatre in Malaysia - Loo, Fung Chiat; Loo, Fung Ying; Toon, Elaine Swan Chien (2016)
Deriving from the Western art form, musical theatre by local Malaysian productions has been increasing since the last decade. The multiculturalism of the community is also reflected in the growing trend of local bilingual musicals. Bilingual use in various art forms is not an unfamiliar phenomenon in Malaysia since it is a multicultural country that consists of three main ethnicities: Malay, Chinese and Indian. This paper highlights and discusses the structure and the musical style employed in bilingual musical productions in Malaysia. Analysis of several productions shows the function of language in these musicals and how bilingualism is used to construct the architecture of a musical.